Localized Neuron Stimulation with Organic Electrochemical Transistors on Delaminating Depth Probes. (30th June 2015) - Williamson, Adam; Ferro, Marc; Leleux, Pierre; Ismailova, Esma; Kaszas, Attila; Doublet, Thomas; Quilichini, Pascale; Rivnay, Jonathan; Rózsa, Balázs; Katona, Gergely; Bernard, Christophe; Malliaras, George G.
<x xml:space="preserve">Abstract</x> Organic electrochemical transistors are integrated on depth probes to achieve localized electrical stimulation of neurons. The probes feature a mechanical delamination process which leaves only a 4 μm thick film with embedded transistors inside the brain. This considerably reduces probe invasiveness and correspondingly improves future brain‐machine interfaces.